2005
DOI: 10.1016/j.agrformet.2005.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A climatological study of the Keetch/Byram drought index and fire activity in the Hawaiian Islands

Abstract: thank you for your friendships and the useful meteorological discussions that we have had. Finally, I would like to extend my gratitude to all ofthe graduate students for making this an enjoyable two years. For the first time, the climatological relationship between the KBDI and fire activity is examined using a number ofdifferent techniques. The KBDI is tested separately on four major Hawaiian Islands against total acres burned (TAB). This relationship is explored using various statistical methods and a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 15 publications
0
39
0
2
Order By: Relevance
“…KBDI is initialized when the soil is at field capacity = 200 mm. It has been successfully applied in tropical climates [46].…”
Section: Meteorological Fire Danger Indices (Fdi)mentioning
confidence: 99%
“…KBDI is initialized when the soil is at field capacity = 200 mm. It has been successfully applied in tropical climates [46].…”
Section: Meteorological Fire Danger Indices (Fdi)mentioning
confidence: 99%
“…Denklemlerde; P, kuraklık etmeni hesaplanacak günün yağış tutarını (mm); T mak , günlük maksimum hava sıcaklığını (°C); P 24 , son 24 saatteki toplam yağışı (mm); yıı P , yıllık ortalama yağış tutarını (mm); kf(t), t zamanındaki kuraklık etmenini; I, KBDI değerini gösterir (Keetch ve Byram, 1968;Janis ve ark., 2002;Goodrick, 2003;Dolling, 2005;Altan ve ark., 2011).…”
Section: Yöntemunclassified
“…The most important feature of the index is to establish a link between drought conditions and forest fires by using the soil moisture content, maximum air temperature and precipitation data in order to determine the days of having a risk for forest fires (Keetch and Byram, 1968). Depending on the weather is rainy or virtually rainless; KBDI value is calculated by considering many specific criterions for making an objective decision (Keetch and Byram, 1968;Alexander, 1990;Heim, 2002;Goodrick, 2003;Dolling et al, 2005;Yamak, 2006;Türkeş et al, 2011a;Türkeş and Altan, 2012abc).…”
Section: Methodsmentioning
confidence: 99%
“…In a 17-month study, Burgan (1976) found that KBDI correlated well with fuel moisture content of the grass Pennisetum setaceum and the native shrub Dodonaea viscosa in Hawai'i (r ¼ À0.82 and À0.84, respectively); however, correlation with Andropogon virginicus was poor (r ¼ À0:21). Dolling et al (2005) reported a strong correlation between KBDI and monthly total area burned from 1976 to 1996 for the islands of O'ahu, Maui, and Hawai'i.…”
Section: Literature Reviewmentioning
confidence: 99%